Second-step lectotypification and a new synonym of Pycnarrhena pleniflora (Menispermaceae) - Arigela, Ravi Kiran; Singh, Rajeev Kumar (Phytotaxa, 2018)
The name Pycnarrhena pleniflora was inadvertently lectotypified before 2001 and therefore it requires second-step lectotypification which is proposed here. The recently described species Drypetes kalamii (Putranjivaceae/Euphorbiaceae s.l.) is treated here as its synonym.